A Comparative Study of Vibrations of Elasto-Viscoplastic Shells and Plates - Kłosowski, P.; Woźnica, K.; Weichert, D. (Engineering Transactions, 1995)
A method of solution of the problem of nonlinear vibrations of elasto-viscoplastic plates and shells is presented, based on the first order shear deformation-moderate rotation theory of the laminated shells. Viscoplastic material behaviour is taken into account by the models developed by Perzyna, Chaboche and Bodner-Partom, respectively. The equations of motion are integrated by the central difference method, while the constitutive equations are integrated by the trapezoidal rule in an iterative process. In both cases the same time step is used. Numerical examples and comparison with experimental results are presented.